Microbial Fuel Cell United with Other Existing Technologies for Enhanced Power Generation and Efficient Wastewater Treatment - Sanchita Bipin Patwardhan (MDPI AG, 2021)
Nowadays, the world is experiencing an energy crisis due to extensive globalization and industrialization. Most of the sources of renewable energy are getting depleted, and thus, there is an urge to locate alternative routes to produce energy efficiently. Microbial fuel cell (MFC) is a favorable technology that utilizes electroactive microorganisms acting as a biocatalyst at the anode compartment converting organic matter present in sewage water for bioelectricity production and simultaneously treating wastewater. However, there are certain limitations with a typical stand-alone MFC for efficient energy recovery and its practical implementation, including low power output and high cost associated with treatment. There are various modifications carried out on MFC for eliminating the limitations of a stand-alone MFC. Examples of such modification include integration of microbial fuel cell with capacitive deionization technology, forward osmosis technology, anaerobic digester, and constructed wetland technology. This review describes various integrated MFC systems along with their potential application on an industrial scale for wastewater treatment, biofuel generation, and energy production. As a result, such integration of MFCs with existing systems is urgently needed to address the cost, fouling, durability, and sustainability-related issues of MFCs while also improving the grade of treatment received by effluent.